Sactive Noise Control Technique Application in Air Conditioning Ducts - Decruz, Aloysius (2009)
Active Noise Control (ANC) is a technique for reducing noise by destructive interference of noise sound wave by out-of-phase secondary sound wave. In air conditioning installations, high frequency noises are effectively attenuated by porous-structured medium; but the low frequency noise produced by the fan needs a more sophisticated approach. An algorithm, ‘Hardware-Tuned Feedback ANC (HTFA)’, has been developed to implement the ANC technique for the noise reduction application in an air conditioning duct element, where Digital Signal Processing is used to sample noise and produce a complete anti-phase noise produced by the HTFA algorithm. Typical blade pass frequency in the vicinity of 100 Hz require sampling frequency of minimum twice that value. A 600 MHz fixed point Digital Signal Processor (DSP) from Texas Instrument, TMS320C6416DSK, is used to generate a secondary sound field by using an adaptive algorithm of Least Mean Square (LMS) principle for convergence. A duct section is used for the experiment and the effectiveness of low frequency attenuation by the secondary sound field is measured. Low and medium frequency tonal noises of octave bands 63 Hz – 1000 Hz were tested, low frequency below 250 Hz being the range of interest. Optimum frequency values for which ANC is more effective are determined. It was found that Active Noise Cancellation is effective at 63 Hz and 125 Hz. This is a simple, economic and effective method for noise cancellation compared to existing feed-forward software tuned method.